The predation relationship between online medical search and online medical consultation—empirical research based on Baidu platform data - Wang, Yang; Ran, Lingshi; Jiao, Wei; Xia, Yixue; Lan, Yuexin (Frontiers in Public Health, 2024)
Introduction This study investigates the mutual influence between online medical search and online medical consultation. It focuses on understanding the health information needs that drive these health information-seeking behaviors by utilizing insights from behavioral big data. Methods We used actual behavioral data from Chinese internet users on Baidu platform’s “Epidemic Index” from November 26, 2022, to January 25, 2023. Data modeling was conducted to ensure the reliability of the model. Drawing on the logistic model, we constructed a foundational model to quantify the evolutionary patterns of online medical search and online medical consultation. An impact function was defined to measure their mutual influence. Additionally, a pattern detection experiment was conducted to determine the structure of the impact function with maximum commonality through data fitting. Results The analysis allowed us to build a mathematical model that quantifies the nonlinear correlation between online medical search and online medical consultation. Numerical analysis revealed a predation mechanism between online medical consultation and online medical search, highlighting the role of health information needs in this dynamic. Discussion This study offers a novel practical approach to better meet the public’s health information needs by understanding the interplay between online medical search and consultation. Additionally, the modeling method used here is broadly applicable, providing a framework for quantifying nonlinear correlations among different behaviors when appropriate data is available.